Interaction of Hb South Florida (codon 1; GTG -> ATG) and HbE, with beta-thalassemia (IVS1-1; G -> A): expression of different clinical phenotypes - Tan, J.; Tan, K.L.; Omar, K.Z.; Chan, L.L.; Wee, Y.C.; George, E. (2009)
Interactions of different hemoglobin variants with thalassemia alleles can result in various clinical phenotypes. HbE-beta-thalassemia generally manifests with severe anemia where individuals exhibit beta-thalassemia major with regular blood transfusions or beta-thalassemia intermedia with periodic blood transfusions. This study presents a unique Malay family with three beta-globin gene defects-HbE, Hb South Florida, and IVS1-1 (G -> A). HbE activates a cryptic splice site that produces non-functional mRNAs. Hb South Florida is a rare beta-hemoglobin variant, and its interactions with other beta-thalassemia alleles have not been reported. IVS1-1 is a Mediterranean mutation that affects mRNA processing giving rise to beta(o)-thalassemia. Fifteen mutations along the beta-globin gene complex were analyzed using the amplification refractory mutation system. Hb South Florida was identified by direct sequencing using genomic DNA The affected child with HbE/IVS1-1 produced a beta-thalassemia major phenotype. Compound heterozygosity for Hb South Florida/IVS1-1 produced a beta-thalassemia carrier phenotype in the mother.